Doing Good while Killing: Why Some Insurgent Groups Provide Community Services - Asal, Victor (Terrorism and political violence, 2022)
Many nonstate military organizations provide a wide range of social services to civilians. The apparent contradiction between their use of violence and their provision of charity has been the subject of a great deal of research in the conflict studies literature. Two of the most common sets of arguments hold that such services are either a form of bribery aimed at controlling and isolating constituents and potential recruits, or an extension of the organization’s ideological commitments. Our findings, based on a new analysis of the BAAD dataset, demonstrate that neither explanation is correct. Rather, we find that the provision of social services represents a means of confronting and undermining the authority of the state. In this sense, the provision of social services represents an extension of the broader political goals of the nonstate armed groups providing them.